Genotype-Phenotype Analysis in Pediatric Patients with Distal Renal Tubular Acidosis - Eujin Park; Myung Hyun Cho; Hye Sun Hyun; Jae Il Shin; Joo Hoon Lee; Young Seo Park; Hyun Jin Choi; Hee Gyung Kang; Hae Il Cheong (Karger Publishers, 2018)
Background/Aims: Primary distal renal tubular acidosis (dRTA) in children is a rare genetic disorder, and three causative mutated genes have been identified: SLC4A1, ATP6V1B1, and ATP6V0A4. We analyzed the prevalence and phenotypic differences of genetic mutations in children with dRTA. Methods: A total of 17 children with dRTA were enrolled in the study. All patients underwent genetic testing for all three candidate genes. Results: Pathogenic mutations, including six novel mutations, were detected in 15 (88.2%) patients: dominant SLC4A1 mutations in ten (58.8%) patients, recessive ATP6V0A4 mutations in three (17.6%) patients, and recessive ATP6V1B1 mutations in two (11.8%) patients. Compared to other patients, patients with SLC4A1 mutations showed an older age of onset (3.7 ± 2.6 years) and less severe metabolic acidosis at initial presentation. All patients developed nephrocalcinosis, and sensorineural hearing loss was observed in two patients with ATP6V1B1 mutations. Three (17.6%) patients had decreased renal function (chronic kidney disease stage 2), and five (29.4%) patients had persistent growth retardation at the last follow-up. Long-term prognosis showed no genotype-phenotype correlation. Conclusions: SLC4A1 is the most common defective gene in Korean children with dRTA. Patients with SLC4A1 mutations show later onset and milder disease severity. Long-term follow-up of hearing ability, renal function, and growth is necessary for patients with dRTA.